Analysis Of Promotion and Service Quality on Customer Satisfaction at The Center Of Hajj and Umrah Souvenirs Bin Daud Makassar - Muliati Muliati; Mochtar Lutfi; Hermawaty Remba Kasim; Vebby Anwar; Dwi Putri (Return : Study of Management, Economic and Bussines, 2023)
This study aims to analyze the effect of promotion on customer satisfaction, the effect of service quality on customer satisfaction, the influence of promotion and service quality simultaneously affect customer satisfaction, and analyze the magnitude of the influence of promotion and service quality on customer satisfaction at the Hajj and Umrah Bin Daud Souvenir Date Center in Makassar City. This type of research is quantitative with research for two months (January-February 2023). The sample in this study was 95 respondents taken using the slovin technique. The analytical methods used are instrument tests (validity and reliability tests), classical assumption tests (normalist tests, multicolonierity tests and heteroscedasticity tests), multiple linear regression tests, determination coefficient analysis and hypothesis testing (persial and simultaneous tests) with SPSS version 25 applications. The results showed that promotion has a positive and significant effect on customer satisfaction, service quality has a positive and significant effect on customer satisfaction, promotion and service quality simultaneously affect customer satisfaction, and promotion and service quality show an influence on customer satisfaction Hajj and Umrah Bin Daud Date Center in Makassar City.